[6×(12:a+7×8):3-2×9]×7+2×39=792
Vă rog repede am nevoie acum!!!!
Răspunsuri la întrebare
Răspuns de
4
[6 × ( 12 : a + 7 × 8 ) : 3 - 2 × 9 ] × 7 + 2 × 39 = 792
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 + 78 = 792
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 = 792 - 78
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 = 714
6 × ( 12 : a + 56 ) : 3 - 18 = 714 : 7
6 × ( 12 : a + 56 ) : 3 - 18 = 102
6 × ( 12 : a + 56 ) : 3 = 102 + 18
6 × ( 12 : a + 56 ) : 3 = 120
6 × ( 12 : a + 56 ) = 120 x 3
6 × ( 12 : a + 56 ) = 360
12 : a + 56 = 360 : 6
12 : a + 56 = 60
12 : a = 60 - 56
12 : a = 4
a = 12 : 4
a = 3
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 + 78 = 792
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 = 792 - 78
[ 6 × ( 12 : a + 56 ) : 3 - 18 ] × 7 = 714
6 × ( 12 : a + 56 ) : 3 - 18 = 714 : 7
6 × ( 12 : a + 56 ) : 3 - 18 = 102
6 × ( 12 : a + 56 ) : 3 = 102 + 18
6 × ( 12 : a + 56 ) : 3 = 120
6 × ( 12 : a + 56 ) = 120 x 3
6 × ( 12 : a + 56 ) = 360
12 : a + 56 = 360 : 6
12 : a + 56 = 60
12 : a = 60 - 56
12 : a = 4
a = 12 : 4
a = 3
Alte întrebări interesante
Istorie,
8 ani în urmă
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă